ASSESSMENT OF CHANGES IN AIR TEMPERATURE AND ATMOSPHERIC PRECIPITATION IN CONDITION OF CLIMATE CHANGE (Andijan region) (Scientific journal of the Fergana State University, 2024)
The article presents the results of a study of air temperature trends and precipitation data associated with global warming and climate change. For 1991-2020, data on air temperature and precipitation were collected at four meteorologic stations. As a result of the study, there was a trend of increasing long-term average air temperatures, while at all stations there was a significant trend of decreasing precipitation. In particular, the amount of precipitation decreased in Andijan (42 mm), Kurgantepe (72 mm), Bose (21 mm) and Ulugnor (18 mm).